2022
DOI: 10.1021/acs.jafc.2c01608
|View full text |Cite
|
Sign up to set email alerts
|

Coexposure of Cyclopiazonic Acid with Aflatoxin B1 Involved in Disrupting Amino Acid Metabolism and Redox Homeostasis Causing Synergistic Toxic Effects in Hepatocyte Spheroids

Abstract: Cyclopiazonic acid (CPA), an emerging toxin, has been found in various foods such as corn, peanuts, and figs.Aspergillus flavus can produce CPA, leading to coexposure with highly toxic aflatoxin B1 (AFB1), but the mechanism of their combined action is not clear. In this study, cocultured hepatocyte spheroids were used as the evaluation model, and two concentration settings of isotoxicity and different toxicity ratios were used to investigate the combined toxic effects. Metabolomics was subsequently used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…To date, multiple studies have revealed the potential mechanisms of Bacillus species for the degradation of mycotoxins. , In this study, integrated metabolomics and transcriptomics analysis were used to explore the differential metabolites and DEGs in B. amyloliquefaciens ZG08 in relation to AFB 1 degradation or response to AFB 1 stress. Previous studies have highlighted the pivotal role of amino acid metabolism in the cellular response to adverse environmental conditions . Significant changes were noted in pathways such as alanine, aspartate, and glutamate metabolism, tryptophan metabolism, and arginine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple studies have revealed the potential mechanisms of Bacillus species for the degradation of mycotoxins. , In this study, integrated metabolomics and transcriptomics analysis were used to explore the differential metabolites and DEGs in B. amyloliquefaciens ZG08 in relation to AFB 1 degradation or response to AFB 1 stress. Previous studies have highlighted the pivotal role of amino acid metabolism in the cellular response to adverse environmental conditions . Significant changes were noted in pathways such as alanine, aspartate, and glutamate metabolism, tryptophan metabolism, and arginine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study, the authors observed different interactions associated with the co-exposure of AFB1 with cyclopiazonic acid (CPA) compared with those reported in the literature. Synergistic effects were obtained in co-cultured hepatocyte spheroids at concentrations close to real-life exposure levels (0.625 µg/mL AFB1 and 3.125 µg/mL CPA) [ 134 ], and the authors speculated that this could be because the 3D culture environment might confer metabolic processes that differ from those of adherent cells, leading to differences in interactions between 3D and 2D cells. Since it is widely accepted that the carcinogenic and toxic effects of AFB1 are dependent on its metabolic activation [ 135 ], 3D cell culture seems to be a complex and suitable model for a more precise evaluation of mycotoxin co-exposure.…”
Section: Applications Of Advanced In Vitro Models For Mycotoxin Asses...mentioning
confidence: 99%
“…Individual and combined cell viability, mitochondria, oxidative stress, metabolomic analysis [134] STE Human neuroblastoma spheroids (SH-SY5Y and SK-N-DZ cells)…”
Section: Afb1mentioning
confidence: 99%